2015
DOI: 10.1097/dss.0000000000000242
|View full text |Cite
|
Sign up to set email alerts
|

Mohs Micrographic Surgery for the Treatment of Hidradenocarcinoma

Abstract: Mohs micrographic surgery seems to be a useful treatment modality for HAC. This is the largest reported series of HAC treated with MMS with long-term follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…In a study by Stanislav et al, the authors performed a retrospective review of hidradenocarcinoma patients treated with Mohs micrographic surgery at Mayo clinic from 1993 to 2013 and they found that Mohs micrographic surgery seems to be a useful treatment modality and there was no recurrence, metastasis and disease related mortality in patients treated with Mohs micrographic surgery. 13 In contrary a case report by Lalya et al, they have concluded that adjuvant therapy should be considered postoperatively for improved loco-regional control and should be mandatory in certain histopathological features like dermal lymphatic invasion, perineural invasion, high anaplastic morphology, extracapsular lymph nodal extension, infiltration of deep structures and positive surgical margins. 8 Their patient was initially treated with only surgery and had recurrence within 5 months of surgery and this recurrence was managed successfully by high dose radiotherapy.…”
Section: Discussionmentioning
confidence: 74%
“…In a study by Stanislav et al, the authors performed a retrospective review of hidradenocarcinoma patients treated with Mohs micrographic surgery at Mayo clinic from 1993 to 2013 and they found that Mohs micrographic surgery seems to be a useful treatment modality and there was no recurrence, metastasis and disease related mortality in patients treated with Mohs micrographic surgery. 13 In contrary a case report by Lalya et al, they have concluded that adjuvant therapy should be considered postoperatively for improved loco-regional control and should be mandatory in certain histopathological features like dermal lymphatic invasion, perineural invasion, high anaplastic morphology, extracapsular lymph nodal extension, infiltration of deep structures and positive surgical margins. 8 Their patient was initially treated with only surgery and had recurrence within 5 months of surgery and this recurrence was managed successfully by high dose radiotherapy.…”
Section: Discussionmentioning
confidence: 74%
“…Wide surgical excision with at least 2–3 cm has been advocated in some reports. If wide margins cannot be achieved because of anatomical or functional conditions, Mohs micrographic surgery can be used to control a subtle extension of the tumor [ 11 ]. Because of the high tendency for regional lymph node metastasis, prophylactic lymph node dissection has been reported [ 12 ], but this aggressive approach has remained controversial since a long-term benefit has not been clearly demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Mohs micrographic surgery has been shown to have superior cure rates in NMSC and is being increasingly used to treat melanoma and other cutaneous malignancies . A complete description of the MMS technique is out of the scope of this article .…”
Section: Discussionmentioning
confidence: 99%